Kur’an’da felah kavramının din eğitimi açısından tahlili - Dağ, Nurullah (My University, 2010)
YOĞUN BAKIM ÜNİTELERİNDE BASI YARASI PREVALANSI VE BASI AZALTICI ARAÇ KULLANIMINA İLİŞKİN MEVCUT DURUM Çalışma erişkin yoğun bakım ünitelerinde bası yarası prevalansı ve bası azaltıcı destek yüzey kullanımına ilişkin mevcut durumu saptamak amacıyla yapıldı. Araştırmaya İstanbul ilinde 50 yoğun bakım ünitesinde, 422 erişkin hasta dahil edildi. Veriler Yoğun Bakım Ünitesi Değerlendirme Formu, Kullanıcı Memnuniyeti Formu, Hasta Değerlendirme Formu, Braden Ölçeği, Hasta Memnuniyeti Formu ile elde edildi. İstatistiksel değerlendirmede SPSS 11.5 versiyonu kullanıldı. Çalışmada Braden Ölçeği’nin sensitivite puanları yüksek olmasına rağmen, spesifite puanları düşük bulundu. Erişkin yoğun bakım ünitelerinde bası yarası prevalansı evre 1 dahil edildiğinde %39,5 iken, evre 1 hariç tutulduğunda %26,3 olarak saptandı. Bası yarası oranları, bası azaltıcı destek yüzey türlerine göre farklılık göstermedi. Havalı yatak örtüsünde sakral bölgede, viskoelastik destek yüzeyde topuk bölgesinde bası yarası oluşumunun daha fazla olduğu saptandı. Sonuç olarak ülkemizde yoğun bakım ünitelerinde bası yarası prevalansının uluslarası literatüre göre oldukça yüksek olduğu ve destek yüzeyler başta olmak üzere önleyici girişimlere odaklanılması gerektiği görülmüştür. Bası azaltıcı destek yüzey, bası yarası, prevalans, yoğun bakım ünitesi ANALYSIS OF THE CONCEPT OF SALVATION IN QUR’AN IN TERMS OF RELIGIOUS EDUCATION Nurullah DAĞ

Salvation refers to one’s attainment of success and happiness in the world and eternal prosperity in the afterlife by fulfilling his religious and moral duties. Also it could be said that it is one’s achievement of endless happiness in the eternal life as the result of true belief and deeds. In the first chapter of this study salvation and concepts that relate to salvation were inspected. Most prominently the concept of “felah” and others such as “fevz”, “necat” and “hidayet” are used in the meaning of salvation. With these concepts it is the the happiness in the afterlife that is more frequently referred. However, for this happiness the belief and deeds in this life matters most. The first verses of the Surah al-Mu’minun concurs with this thesis. In these verses it is told that believers that quit vain deeds, having their prayers in awe and distribute alms will reach to salvation. “Successful indeed are the believers. Those who offer their Salât (prayers) with all solemnity and full submissiveness. And those who turn away from Al-Laghw (dirty, false, evil vain talk, falsehood, and all that Allah has forbidden)” (Surah Al-Mu’minun; 1-3). In this chapter, concepts that relate to salvation in such verses were expressed in their both terminological and idiomatic meanings. Furthermore, in the second chapter the elements that lead a person to salvation were dealt with in three parts. Starting with the principles of belief, with worshiping and the collectivity of the moral elements a general framework of salvation was described. In addition in order to attain salvation, insufficiency of the sole acceptance of the principles of faith and the certain need for the integration of this faith with worshiping and moral principles was given as the consequence. So much so that, those who commit the righteous deeds (salih ameller) will reach happiness in both this world and the afterlife. Islam is a religion of integrity. Therefore none of the elements in the religion could be abandoned for another. Hence; keeping the idea of integrity in mind, the elements of salvation too has to be taken and applied within such a framework. Salvation, Faith, Deeds, Harm
Keywords: Din Eğitimi; Kur’an-ı Kerim